Diamonds, gold, and war : the British, the Boers, and the making of South Africa - Meredith, Martin (PublicAffairs, 2007)
A history of the tumultuous period leading up to the 1910 founding of the modern state of South Africa explores how the discovery of vast diamond and gold deposits led to a fierce struggle between the British and the Boers for control of the region.